Efficacy of azvudine plus dexamethasone in severe hospitalized patients with Omicron infection: a prospective multicenter study - Zhang, Meng-Lan; Wei, Xiao-Ying; Su, Nan; Jiang, Jung-Hong; Xu, Guo-Peng; Zeng, Da-Xiong (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAzvudine (AZV), the first Chinese oral anti-coronavirus disease 2019 (COVID-19) drug, has shown substantial clinical benefits to viral clearance and prognosis in patients with mild and common COVID-19. However, there is no evidence in severe hospitalized COVID-19 patients.MethodsIn this multicenter study, we analyzed 209 severe hospitalized COVID-19 patients in four hospitals. All the clinical data and the 28-day composite outcomes were recorded. All of the patients were categorized into two groups according to drug: the dexamethasone (DXM) group and the azvudine plus dexamethasone (AZV+DXM) group.ResultsThere were no differences in sex, age, BMI, and underlying diseases between the two groups. The ratio of the 28-day composite outcome was lower for the AZV+DXM group than that for the DXM group (16.97% vs. 31.82%, p = 0.029). The viral clearance time was shorter in the AZV+DXM group than in the DXM group (7.32 ± 2.57 vs. 8.55 ± 2.34 days, p = 0.017). The PaO2/FiO2 levels on day 5 (258.89 ± 55.22 vs. 233.12 ± 60.51, p = 0.026) and day 10 (289.48 ± 44.09 vs. 261.52 ± 37.34, p = 0.015) were higher in the AZV+DXM group than the DXM group. However, data on the hospitalization duration of the two groups were similar. Cox analysis showed the benefit of AZV+DXM in the subgroups of ≥65 years old, multiple organ dysfunction syndrome (MODS), cerebrovascular disease, C-reactive protein (CRP) ≥70mg/L, and D-dimer ≥1 µg/L.ConclusionThis study is the first to indicate that treatment with AZV+DXM might benefit severe Omicron-infected patients compared with DXM treatment alone. This finding demonstrates, at least partly, the necessity of antiviral treatment in severe patients.